Pengaruh Pemanfaatan Dana Zakat dalam Mengentaskan Pertumbuhan Ekonomi Serta Kemiskinan di Provinsi Sumatera Utara - Naili Nuril Aufa Manik; Miftakhul Choiri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Poverty reduction in Indonesia is the government's main focus in achieving the goals of economic development and better welfare of the population. In the Islamic context, there is an order to pay zakat. As a country with a majority Muslim population, it is hoped that the implementation of zakat can be a solution to overcome the problem of poverty. The obligation to pay zakat is an integral part of Muslim religious practice. This research aims to explore how the management and use of zakat can play a role in reducing poverty in North Sumatra Province. The research method used is quantitative. The research results show that variable population growth does not have a significant influence on zakat, with a probability value of 39%. However, variable poverty shows a significant influence on zakat.